Implications of hybridisation and cytotypic differentiation in speciation assessed by AFLP and plastid haplotypes: a case study of Potentilla alpicola La Soie - Paule, Juraj; Scherbantin, Antonia; Dobeš, Christoph (BMC evolutionary biology, 2012)
Hybridisation is presumed to be an important mechanism in plant speciation and a creative evolutionary force often accompanied by polyploidisation and in some cases by apomixis. The Potentilla collina group constitutes a particularly suitable model system to study these phenomena as it is morphologically extensively variable, exclusively polyploid and expresses apomixis. In the present study, the alpine taxon Potentilla alpicola has been chosen in order to study its presumed hybrid origin, identify underlying evolutionary processes and infer the discreteness or taxonomic value of hybrid forms.